Humoral and cellular immunity in response to an in silico-designed multi-epitope recombinant protein of Theileria annulata - Abid, Asadullah; Khalid, Ambreen; Suleman, Muhammad; Akbar, Haroon; Hafeez, Mian Abdul; Khan, Jawaria Ali; Rashid, Muhammad Imran (Frontiers in Immunology, 2024)
Tropical theileriosis is a lymphoproliferative disease caused by Theileria annulata and is transmitted by Ixodid ticks of genus Hyalomma. It causes significant loss in livestock, especially in exotic cattle. The existing methods of its control by chemotherapeutic agents and available vaccine, based on attenuated schizont staged parasite, have several limitations. A promising solution to control this disease is the use of molecular vaccines based on potential immunogenic proteins of T. annulata. For this purpose, we have selected 5 antigenic sequences of T. annulata i.e. SPAG-1, Tams, TaSP, spm2 and Ta9. These were subjected to epitope prediction for Cytotoxic T-lymphocytes, B-cells and Helper T-lymphocytes. The epitopes having higher score for CTL and B-cell epitopes; and least percentile score for HTL epitopes were selected. A single protein was constructed using specific linkers and evaluated for higher antigenicity and least allergenicity. The construct was acidic, hydrophobic and thermostable in nature. Secondary and tertiary structures of this construct were drawn from PSIPred and RaptorX servers respectively. The Ramachandran plot shows a high percentage of residues of this construct in favorable, allowed and general region. Molecular docking studies suggest that the complex is stable and our construct could be potentially a good candidate for immunization trials. Further we have successfully cloned it to pET-28a plasmid and transformed it in BL21 strain. A restriction analysis was performed to confirm the transformation of our plasmid. After expression and purification, recombinant protein of 49kDa was confirmed on western blot. ELISA results detected raised specific antibody levels in immunized animals' sera when compared to control group and flow cytometric analysis shows the stronger cell mediated immune response. We believe our multi-epitope recombinant protein has the potential for the large-scale application for disease prevention globally in bovine population. This study will act as a model for similar parasitic challenges.